SYNTHESIS OF ENANTIOPURE MORPHOLINES THROUGH THE POST-UGI TRANSFORMATIONS - Almagambetova, Kamila (Nazarbayev University School of Sciences and Humanities, 2022)
It is well known that the field of modern organic chemistry has been developing extremely fast. Thus, elaboration of new methodologies and enlargement of the efficacy of complex compositions at minimal self-cost and environmental damage are considered as main priorities of development of organic synthesis. One of the advancements of organic synthesis are multicomponent reactions. Multicomponent reactions (MCRs) are converging chemical modifications that allow the formation of an assembly of three or more chemical reactants in one operation to produce a complex structure [1]. Such reactions have been widely utilized in medicinal and organic chemistry due to their significant potential to synthesize diverse libraries of compounds, especially in diversity-oriented synthesis (DOS) [2]. The superiority of such reactions is an ability to reduce number of operations and purification of obtained compounds, thus providing an adduct having minimal atom loss. In addition, multicomponent reactions decrease the use of organic solvents and waste production, having a positive influence on environmental chemistry. Since MCRs have a significant potential to incorporate several building blocks in one complex framework in the concept of DOS, they can be tuned towards the generation of a library of heterocyclic molecules straight through Ugi or corresponding post-modifications
Keywords: Type of access: Restricted; organic chemistry; enantiopure morpholines